Effective bracing system for telecommunication towers - Fatin Atiqah, Rasdin (2019)
Nowadays, towers with four-legged self-supporting system are widely used worldwide for wireless and broadcast communication purpose. However the major concern is the failure of such structure in a disaster since in wireless communication network these kinds of towers play a significant role. Thus, all these tendencies of extreme conditions are considered for designing such towers are of the utmost importance. This study was carried out to determine the effects of different heights of towers at 30 m, 40 m, 50 m, and 60 m as well as different types of bracing systems such as K and Y with respect to the wind load acting on the towers. The wind speeds considered in this study were 33.5 m-1 and 44.0 ms-1. The wind modelling and simulation of the tower was conducted using commercial available software STAAD. ProV8i. The results were compared in terms of displacement and member stress. Based on the result obtained, the displacement of towers with Y bracing system was found lesser than K bracing system approximately 36% while the member stress of the tower with K bracing system was found more than Y bracing system about 56% at wind speed 44.0 ms-1.